2012
DOI: 10.1242/dev.076018
|View full text |Cite
|
Sign up to set email alerts
|

Six3 cooperates with Hedgehog signaling to specify ventral telencephalon by promoting early expression of Foxg1a and repressing Wnt signaling

Abstract: SUMMARYSix3 exerts multiple functions in the development of anterior neural tissue of vertebrate embryos. Whereas complete loss of Six3 function in the mouse results in failure of forebrain formation, its hypomorphic mutations in human and mouse can promote holoprosencephaly (HPE), a forebrain malformation that results, at least in part, from abnormal telencephalon development. However, the roles of Six3 in telencephalon patterning and differentiation are not well understood. To address the role of Six3 in tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…S6). Similar to the results reported in zebrafish (Carlin et al, 2012), Six3 appears to transiently regulate Foxg1 expression during the early stages of mouse embryonic development.…”
Section: Six3 Directly Regulates Foxg1 Expression In the Anterior Neusupporting
confidence: 85%
See 3 more Smart Citations
“…S6). Similar to the results reported in zebrafish (Carlin et al, 2012), Six3 appears to transiently regulate Foxg1 expression during the early stages of mouse embryonic development.…”
Section: Six3 Directly Regulates Foxg1 Expression In the Anterior Neusupporting
confidence: 85%
“…catenin signaling pathways during dorsoventral patterning of the telencephalon (Danesin et al, 2009;Sylvester et al, 2013). Briefly, Shh activates foxg1 expression in the ventral forebrain and, in turn, Foxg1 is cell-autonomously required for the specification of the ventral telencephalon; Foxg1 also restricts the dorsal telencephalon by repressing wnt8b expression (Danesin et al, 2009). Carlin et al (2012 showed that, in zebrafish, six3 cooperates with Hh signaling to promote Foxg1 expression during dorsoventral patterning of the telencephalon.…”
Section: Six3 Directly Regulates Foxg1 Expression In the Anterior Neumentioning
confidence: 99%
See 2 more Smart Citations
“…5C). In mice, both Pax6 and Six3 genes are essential for the appropriate forebrain patterning (37)(38)(39)(40). As expected, PAX6 and SIX3 centering in the hub generated the most connections with other modules (Fig.…”
Section: Determinant Stages Controlling Hesc Neural Differentiationmentioning
confidence: 74%